Características dos flocos formados com a utilização de Moringa oleifera como coagulante em água produzida com cor elevada - Ribeiro, Lucas Cordeiro (2021)
Moringa oleifera seeds have been the focus of a lot of researches in many different areas of knowledge including utilization as a natural coagulant in water treatment. In this perspective, the present research aims to deepen knowledge about Moringa oleifera potential as a coagulant and the morphological characteristics of the flocs formed in produced water with high apparent color (107 ± 1 mg Pt-Co/L). Initially, a comparison between the apparent color removal efficiency was made utilizing Dissolved Air Flotation (DAF) and sedimentation. The results showed better performance by using DAF and thus it was used in the remaining steps of the research. Then it was used the coagulation/ flocculation/ DAF assays with different dosages of coagulant and coagulation pH to elaborate coagulation diagrams for different flotation speeds. After this, six points of those diagrams were selected for breakage and reflocculation assays using different mean velocity gradients () and rupture gradients () of 120 and 500 s-1. In these assays, images were obtained using a non-intrusive and non-destructive technique, with the continuous analysis through a Photometric Dispersion Analyzer (PDA) to evaluate Particle Size Distribution (PSD) and fractal dimension during the formation and regrowth of flocs, including the evaluation of their strength and resistance. Moringa oleifera showed effectiveness in high apparent color removal, with many diagram regions over 70% results. For the assays with equal to 120 s-1, variance analysis tests (ANOVA) showed that rupture at this gradient was not enough to significantly alter color removal efficiency. Fractal dimension values varied between 1,66 and 1,96 and had considerable variation after the rupture equal to 500 s-1, suggesting that the uniquely self-similar structure of the flakes is just an ideal concept and that the fractal dimension changes according to the physical conditions of coagulation. Considering the fractal dimension value after coagulation stabilization, it was observed that there was no significant difference between the values for different , showing that the morphological structure tends to keep independent of the diameter and the mixing intensity. In addition, the results traced that the flocs did not fully recover their size.